Are State-Owned Enterprises doing better? An empirical study on climate change mitigation efforts reported by Indonesian companies - Iqram Ramadhan Jamil; Balgis Inayah (Center for Science and Technology, IAIN Surakarta, 2023)
Indonesia is a country with high Greenhouse Gas (GHG) emission, contributing significantly to climate change problems. As part of its commitment to address this, the Indonesian government, through State-Owned Enterprises (SOEs), is dedicated to mitigating climate change. Early reporting on this mitigation efforts is crucial in addressing this pressing issue. This study aims to examine how company ownership and other companies’ characteristics (such as sector type, size, and profitability) influence the disclosure of climate change mitigation efforts. Content analysis is conducted on the annual and sustainability reports of top-100 Indonesian companies, based on their financial performance in 2020. Among the 100 observations, only 13 companies were categorized as have comprehensive reporting. In addition, using the General Ordered Logit Model (GOLM) regression, this study reveals that SOEs do not demonstrate superior disclosure compared to private companies. Instead, industry type and company size notably influence the climate change mitigation efforts, while the company’s profitability shows no significant impact on reporting. Therefore, improving disclosure require stricter regulatory enforcement, especially for SOEs and private companies, business in the low-emissions sectors, and those with limited asset levels.